The Value of Tolerance in Tanbih Implemented through the Covert Curriculum at the Suryalaya Islamic Boarding School, Tasikmalaya - Zamzami, Zaki (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This study explains the values of tolerance through a hidden curriculum based on the teachings of tanbih as a pesantren guideline for teaching the noble values of living in harmony. Tanbih is a testament from the founder of the Pesantren regarding life guidance that all components of the extended family of the Pesantren Suryalaya must carry out. Previous studies have explained that the interaction between teachers and students is an essential element in the success of the hidden curriculum and that certain religious values can affect religious tolerance. Based on this study, researchers argue that cultural/religious values are an important foundation in internalizing tolerance education in schools. In this study, the researchers focused on the value of tanbih as an element of Islamic culture that underlies tolerance education in Pesantren through a hidden curriculum. This study uses a qualitative approach with observation techniques, literature studies, and in-depth interviews. In theoretical analysis, the value of tanbih is an Islamic cultural element that underlies various hidden curriculum components to foster tolerance in students. Cultural/religious values that form the basis of religious education must receive special attention to reduce the potential for intolerant education.